Premeditando o Breque and Lingua de Trapo: the political dimension of Vanguarda Paulista (Sao Paulo Ayala garde) through humor - Fenerick, Jose Adriano [UNESP] (Univ Federal Uberlandia, 2020)
This article is a study of political criticism of the Lingua de Trapo and Premeditando o Breque songs, performed through humor. Inserted in the underground field of the early 1980s, and, therefore, relatively distant from the rules imposed by the great music market in Brazil, these two groups, belonging to the so-called Vanguarda Paulista, created a critical counterpoint to the musical production of their time. Thus, by analyzing some of their songs, this study seeks to highlight some aspects of humor as a procedure of cultural and political criticism.
Keywords: humor; Lingua de Trapo; Premeditando o Breque